Academic Translation: The Impact of Algerian Natural Gas Revenues on the Trade Balance: An Empirical Study Using the Non-linear Autoregressive Distributed Lag Model - Abdelhadi, Hadj Kouider; Abdelkader, Lahciene; Bouamra, Hacene (The journal of contemporary issues in business and government, 2023)
The study aimed to measure the impact of Algerian natural gas revenues on the trade balance during the period (2000-2022). The study utilized the Nonlinear Autoregressive Distributed Lag (NARDL) model to assess the effect of both positive and negative values of natural gas revenues on the trade balance over the short and long terms. The findings indicate that an increase in natural gas revenue in Algeria leads to an increase in the trade balance in both the short and long terms. Conversely, a decrease in total revenues has a negative impact on the trade balance.